(untitled) (Fiep Bulletin - online, 2016)
The capacity of magnetic fields interfere in the electrons flow is described in physics as Hall Effect. This effect happens by changing the bioelectric flow of the body (LENHINGER, 2002), which is directly connected to pain relief (HINMAN; FORD.; HEYl, 2002). The cell plasma membrane is made of molecules that form proteins and enzymes sensible to the action of temperature, ph. and ions flow. The magnetic energy changes the electron flow generating events that affect the cell conformation of molecules in the body, and can change the velocity of cell, enzymatic and organic processes, making chances in the body (HENEINE, 2000). The use of magneto therapy by applying magnetos above the site of inflammation is a therapy with significant effects (SOUZA, 2005), non-invasive, cheap cost and does not cause side effects as anti-inflammatory drugs causes in kidney and digestive systems. OBJECTIVE: investigate how magnetic energy acts in human beings, on theirs joint and muscular inflammation. METHODS: This study will be developed by literature review and analysis of 740 Gauss magnetos use in body parts with joint and muscular pain, applying north and south poles. RESULTS: the use of magneto’s north pole above the inflamed place with pain, causes negative entropy effect through a delicate adjustment on tissue PH (BRAGA; ROSA; ARAUJO, 2004), interfering on electric electron flow of pain information and generating homeostasis in acute cases. The South Pole acts on inflammation process, muscular and joint pain, all of them chronic, decreasing pain and inflammatory process (SCHNEIDER, 2013).